2021
DOI: 10.23887/jpi-undiksha.v10i1.17320
|View full text |Cite
|
Sign up to set email alerts
|

The Process Skills Approach with Mind Map Media Through Lesson Study Improving Students’ Learning Outcomes

Abstract: This study aims to analyze the effectiveness of mindmap-assisted process skills approach through lesson study in improving students' learning outcomes This study uses qualitative approach with descriptive research type. The subjects of this study were students of class VB. Implementation of the lesson study cycle is carried out 13 times cycles, with details of the first lesson study model's eight cycles for the lesson study teacher and the next five cycles for the model teacher. The data collection instruments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The fact that there are activities in each cycle to meet in developing, executing, and performing evaluations together within a few months, capable of producing better learning, and lesson study can enhance teacher competency, is also supported by earlier research (Supriyanto et al, 2020;Annisa et al, 2021). Referring back to earlier study, Seleznyov (2018) found that the method of implementing lesson study in Japan is inextricably linked to the cooperative actions of teachers in lesson planning and reviewing activities that have been used in the teaching and learning process.…”
Section: Ijels 11(2):87-91mentioning
confidence: 88%
See 1 more Smart Citation
“…The fact that there are activities in each cycle to meet in developing, executing, and performing evaluations together within a few months, capable of producing better learning, and lesson study can enhance teacher competency, is also supported by earlier research (Supriyanto et al, 2020;Annisa et al, 2021). Referring back to earlier study, Seleznyov (2018) found that the method of implementing lesson study in Japan is inextricably linked to the cooperative actions of teachers in lesson planning and reviewing activities that have been used in the teaching and learning process.…”
Section: Ijels 11(2):87-91mentioning
confidence: 88%
“…In Japan, lesson study implementation typically takes more than five weeks. This prolonged cycle period aids educators in creating engaging lessons that enhance learning outcomes in the classroom (Annisa et al, 2021;Sudirtha, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Students in learning have their own styles that increase student motivation, increase creativity, so that the learning process can explore developments (Banggur, et al 2018;Solihati, E. 2017;Rienties et al, 2017). In the education variable, performance and strategy are very important learning activities to evaluate (Annisa et al, 2021;Alhassan & Chen, 2019;Bruyckere et al, 2017). Learning in all fields has the same important factors, even though in the era of natural knowledge (science) it is an effort or process to develop a scientific attitude so that it can solve problems in everyday life (Firdaus & Wilujeng, 2018;Grobler, 2018;Pamungkas et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Process skills are very important. Process skills are the basis for doing thinking which provides opportunities for students to experiment directly (Annisa et al, 2021;Desnita & Susanti, 2017;Esi Febrina & Mukhidin, 2019;Fujiyanti et al, 2018;Hayati et al, 2019). Learning outcomes are not only assessed from the mastery of concepts but can be seen from the skills of the learning process which aims to develop a sense of responsibility (Bakri et al, 2019;Elvanisi et al, 2018;Puspita, 2019).…”
Section: Introductionmentioning
confidence: 99%